PREVENTION OF SELF-HARM IN ADOLESCENTS FROM BROKEN HOMES THROUGH MA‘RIFAT AL-NAFS: A THEMATIC STUDY OF QUR’ANIC EXEGESIS - Qinta Berliana Valfini; Made Saihu; Muhammad Ulinnuha (Sekolah Tinggi Agama Islam Sadra, 2025)
The increasing prevalence of self-harm among adolescents from broken homes in Indonesia demonstrates the serious psychological impact of parental divorce, which often triggers emotional instability, anxiety, and destructive behaviors. National surveys indicate that adolescents from divorced families are more vulnerable to depression and self-injury than those from intact families. This study aims to explore the role of ma‘rifat al-nafs (self-awareness) as a Qur’anic-based approach to preventing self-harm in broken-home adolescents. Using a qualitative method with a descriptive-analytical approach, this research applies thematic exegesis of the Qur’an and integrates insights from classical and contemporary tafsir, particularly the thought of al-Ghazālī on self-awareness. The findings reveal that ma‘rifat al-nafs (a deep understanding of self-identity) strengthens emotional resilience by guiding adolescents to understand themselves, accept their circumstances, and transform negative emotions into constructive actions. Its practical application is realized through three techniques: self-talk as reflective dialogue to regulate emotions, self-forgiveness to release guilt and resentment, and self-love to build self-appreciation and positive growth. These techniques align with Qur’anic principles in Q.S. Al-Baqarah [2]: 195 and Q.S. As-Shams [91]: 7—10, which emphasizes the prohibition of self-destruction and the importance of soul purification. In conclusion, ma‘rifat al-nafs provides a spiritual and psychological framework to reduce self-harm tendencies, while its effectiveness requires support from education, community, and social environments. Thus, this study contributes to presenting a Qur’anic solution that integrates spiritual, emotional, and social dimensions to improve the well-being of adolescents from broken homes.